How to reduce perinatal mortality? The contribution of Portuguese reform of perinatal healthcare - Hercília Guimarães (Hygeia Press di Corridori Marinella, 2015)
In 2008, the World Health Organization indicated Portugal as an example to follow in reducing perinatal, neonatal and infant mortalities. The success achieved over the last five decades is a source of pride for the perinatology professionals today. Of paramount importance was the program "Child and Maternal Hospital Healthcare Referral Network", to start in 1990 and to be fulfilled in a decade. The key point made in the document was the classification of hospitals in health care levels with definition of the roles of each one. The goal of the closure of hospitals with few births (less than 1,500 deliveries per year) was successfully achieved, with the closing of about 150 delivery rooms at that time. A neonatal transport in the country started to work in Lisbon, Porto and Coimbra. The aims of regionalization were achieved. The organization in primary, secondary and tertiary healthcare resulted in the improvement of perinatal care centered on both mother and child needs. The perinatal care reform of perinatal care in Portugal is an example of how a good diagnosis and adequate proposals combined with a strong political will are crucial for changing.